2022-RA-1422-ESGO Detailed profiling of the immune microenvironment in ovarian epithelial cancers; relation to tumour characteristics and impact on prognosis. (20th October 2022) - Stout, Annabel; Facey, Natalya; Bhatnagar, Anjali; Rice, Kirstie; Berditchevski, Fedor; Kearns, Daniel; Metcalf, Amy; Shaaban, Abeer M; Elghobashy, Alaa
Abstract : Introduction/Background: Advances in knowledge of tumour microenvironment in various cancers have led to revolutionary immunotherapies and improved patient survival. The profiling of ovarian cancer microenvironment and impact on outcome remain understudied. Methodology: All ovarian cancer patients treated at a large UK Cancer tertiary referral institution over a 5 year period were identified. Included were epithelial ovarian primaries of any stage and grade undergoing primary or interval de-bulking surgery with follow up and tumour paraffin blocks available. Representative tumour blocks were immunohistochemically stained for CD3 (T lymphocytes), CD20 (B lymphocytes), CD68 (pan macrophages) and CD163 (M2 macrophages subtype). Detailed quantitative scoring and topography following the International Immuno-Oncology Group guidelines was done. Results: A total of 138 cases with mean age of 60.5 years were included. 52.9% of cancer cases were WHO stages 3&4 and 72.55% were grade 3. Neoadjuvant chemotherapy was used in 16.7% of cases. After 81 months of follow up, 62.3% of patients were alive with median survival of 41 months. Increased CD3 stromal average was found in grade 3 cancers compared with grades 1 and 2 (p= 0.009) and in higher stage disease (p=0.047). CD3 stromal average correlated positively with patients' age (rs = 0.172, p= 0.044). CD20 stromal average and percentage were statistically higher in high grade tumours (p= 0.009 and p= 0.036 respectively). CD3/CD20 stromal averages and CD20% negatively correlated with survival ([rs= -0.215, p=0.014], [rs= -0.250, p=0.004], [rs= -0.267, p=0.004] respectively). CD68/CD163 expression did not predict tumour characteristics or patient outcome. Conclusion: There was significant association between increased stromal tumour infiltrating lymphocytes and adverse tumour prognosticators and worse patient survival supporting an important role of the tumour microenvironment in prognosis and potential for immunotherapies in ovarian cancer. Further analyses are underway to determine the expression in different tumour types and relation to neoadjuvant chemotherapy response.